Kiss - Wilson, Jacqueline (London : Corgi, 2008)
Fourteen-year-old Sylvie, having dreamt that one day she will marry her best fried Carl, is hurt when she begins to realize that he might be more interested in boys then girls, and when Carl acts on his feelings for his classmate, Paul, and becomes the victim of homophobia, Sylvie and her friend, Miranda, help him overcome the difficult situation.
School Library Journal, March 2010.
Young Adult
Keywords: Emotions in adolescence -- Juvenile fiction; First loves -- Juvenile fiction; Teenagers -- Juvenile fiction; Emotions in adolescence -- Fiction; First loves -- Fiction; Teenagers -- Fiction; Emotions -- Fiction; Love stories; Teenagers -- Fiction; Love stories